Acid-free approach towards the growth of vertically aligned TiO2 nanorods as an efficient photoanode for dye-sensitized solar cells. (September 2018) - Kim, Dong Hyun; Dudem, Bhaskar; Yu, Jae Su
Graphical abstract: Highlights: Vertically aligned TiO2 NRs are fabricated by an acid-free hydrothermal approach. Study the effect of TiO2 NRs growth parameters on its structural/optical properties. The optimized TiO2 NRs were employed as an efficient photoanode for DSSCs. An optimal PCE of 2.45% was achived by DSSC with TiO2 NRs with heights of ∼1.56 μm. Abstract: We synthesized the closely packed titanium dioxide nanorods (TiO2 NRs) on fluorine-doped tin oxide (FTO) glass by a facile and cost-effective hydrothermal method. The TiO2 NRs were further utilized as a photoanode for dye-sensitized solar cells (DSSCs). For hydrothermal growth of TiO2 NRs, we utilized an acid-free reaction medium instead of a strong acidic medium, which can reduce the equipment cost as well as the environmental damages. Before employing these TiO2 NRs for DSSCs as a photoanode, the effects of hydrothermal growth parameters on the structural and optical characteristics of TiO2 NRs/FTO glass were investigated. Eventually, the TiO2 NRs with optimized height and diameter were employed to DSSCs and their photovoltaic characteristics were examined.